Comparative analysis of five brands of lisinopril tablets in Yemeni market - Othman, Gamil Qasem (University of Science and Technology, 2014)
Background: In poor countries such as Yemen, the cost of drugs is a factor affecting the patients decision to buy it and generic medicines are introduced as cheaper alternatives to the high cost brands. However, it has been believed that generic medicines are inferior in quality compared to the branded medicines. Thus, the aim of the present study is to investigate the physicochemical equivalence of five brands of tablets containing Lisinopril (antihypertensive) sourced from different retail pharmacy outlets in the Yemeni market. Methods: The quality and physicochemical equivalence of five different brands of Lisinopril tablets were assessed. The assessment included the evaluation of uniformity of weight, friability, crushing strength, disintegration and dissolution tests as well as chemical assay of the tablets. Results: Results obtained showed that all five brands of the Lisinopril 5 mg tablets passed the British Pharmacopoeia (BP) standards for uniformity of weight, the crushing strength/hardness test and the friability test. All the brands passed the disintegration test and standard assay of content of active ingredients Conclusion: The five brands of Lisinopril 5mg tablets that were analysed passed all the BP quality specifications and were physically and chemically equivalent. All tested formulations were found to be equivalent.